PERBEDAAN PEMBIAYAAN PEMILIKAN RUMAH SYARIAH TANPA BANK DAN PEMBIAYAAN PEMILIKAN RUMAH DENGAN BANK SYARIAH DITINJAU DARI HUKUM EKONOMI SYARIAH DAN HUKUM POSITIF - Dedi Isman; M. Dawud Arif Khan; Abdul Wahab Abd. Muhaimin (MISYKAT Jurnal Ilmu-ilmu Al-Quran Hadist Syari ah dan Tarbiyah, 2025)
This research is based on the fact that there is a housing shortage (backlog) in housing needs in Indonesia which has reached 11 million. One way to fulfill this backlog is sharia home financing using sharia banks and without banks. This research uses qualitative methods with case or field studies using an empirical legal research approach that analyzes and examines legal practices that occur. This research proves that: First, there are differences in the contracts used by sharia property developers without banks and those used by sharia banks. Second, there are differences in the transfer of ownership status in the process of changing the name of a house ownership certificate. Third, in terms of resolving sharia property developer disputes through 2 stages, namely by deliberation or through religious courts, sharia banks go through 3 stages, namely deliberation, through national sharia arbitration bodies and religious courts.